Implementasi Media Audio Visual Pada Pembelajaran Cerita Rakyat Untuk Meningkatkan Keterampilan Berbahasa Siswa Sekolah Dasar - Azka Salsabila; Sukartono Sukartono (Universitas Negeri Padang, 2023)
This study aims to determine the planning, implementation, obstacles and solutions of implementing audio-visual media in learning folklore to improve language skills. The type of research used is a qualitative descriptive research method with data collection techniques in the form of interviews, observation, and documentation. The researcher chose SDN Pajang 3 as the object of research because it is an elementary school that has carried out learning with audio-visual media on several learning materials. Based on the selected object, the subjects in this study were grade 2 students and teachers who were involved in learning with audio-visual media. Information on research subjects in data collection activities in the form of interviews was then analyzed using data analysis techniques which included transcripts of interview results, data reduction, and data interpretation. The results of the study show that in planning lessons with audio-visual media, teachers and students carry out their respective roles in preparing for the implementation of teaching and learning activities properly. The implementation of learning with audio-visual also has a positive impact starting from easier implementation and achieving more functions for students. There are weaknesses in the form of the quality of facilities and infrastructure as well as information that is not optimal with the solutions that have been found and implemented by the teacher. Teachers can also prevent problems from occurring properly and with a complete strategy so that learning continues to run optimally based on the constraints that may occur.